Criminal punishment and early release programs - Corlett, J. Angelo (Sociološki pregled, 2018)
The punishment of criminals is a long-debated topic in penology, criminology, and sociology of law. But it has an underdeveloped history in philosophy generally, and in philosophy of law in particular. Philosophical discussions of early release programs is particularly lacking in philosophy of law and moral philosophy. But in the State of California, there are several citizens who believe that criminals ought to be treated with much more compassion than is currently the case (as they see it) and all that this seemingly implies, while there are those who argue for a compassionate but harsher treatment of criminals. This paper is an attempt to provide some philosophical clarity to some of the legal, economic and moral questions pertaining to whether or not proposed early release programs in California concerning criminal punishment are justifed.